Ethical issues and challenges of purchasing in the wake of the crisis - Vörösmarty, Gyöngyi; Tátrai, Tünde (Vezetéstudomány / Budapest Management Review, 2024)
The focus of this research is to examine how ethics and ethical issues in business procurement in organisations have changed in recent years as a result of the global economic and supply problems. The authors replicated an earlier survey and compared the results. The open-ended questions of the questionnaire detail the responses. The results show that the supply problems of recent years and new challenges for procurement, such as digitalisation, have created new problems for the industry. The literature addresses the issues surrounding the conflict of interest between an owner and a purchaser, or between a purchaser and a supplier. However, the results reveal that ethical conflict impacts a broader spectrum of stakeholders, and they are also reinterpreting traditional ethical problems.